Learning from experience. - Schank, John F. (John Frederic), 1946- (Rand Corporation monograph series., 2011)
"Large, complex submarine design and construction programs demand personnel with unique skills and capabilities supplemented with practical experiences in their areas of expertise. Recognizing the importance of past experiences for successful program management, the governments of the United States, the United Kingdom, and the Commonwealth of Australia asked the RAND Corporation to develop a set of lessons learned from previous submarine programs that could help inform future program managers. In this volume, the authors present an overview of five submarine programs from the three countries--the U.S. Navy's Ohio, Seawolf, and Virginia programs; the UK's Astute program; and Australia's Collins program-- and identify lessons that apply to all of them. The lessons were developed through an extensive literature review and numerous interviews with government and private-sector personnel involved in the programs. Among the most important lessons: Ensure the stability of the program; establish the roles and responsibilities of the government and private-sector organizations; develop knowledgeable and experienced managers; and take a long-term, strategic view of the submarine force and the industrial base"--Publisher description.